1997
DOI: 10.1097/00004872-199715090-00008
|View full text |Cite
|
Sign up to set email alerts
|

Isolated office hypertension and end-organ damage

Abstract: These results, at variance with those of others, suggest that IOH affects the cardiovascular system even during the early phases of the disease and indicate the need for prospective clinical trials to evaluate the benefit from early treatment of IOH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 37 publications
2
12
1
Order By: Relevance
“…Two blood pressure readings were recorded with patients in the sitting position for at least 5 min, between 0900 and 1100 h in the morning; the average of the two readings was considered as the measurement for that visit; twenty-four hour ambulatory blood pressure monitoring (ABPM), by Spacelabs Inc. 90207 (Redmond Washington, USA), during a normal working day, as already published. 11 The monitor was fitted on in the morning, between 1000 and 1200 hours Subjects were asked to perform their normal daily activities and to consume their habitual diet. After calibration, the monitor was programmed to record BP and heart rate (HR) at 15-min intervals during the subjects' waking hours and at 20-min intervals during their usual sleeping hours.…”
Section: Methodsmentioning
confidence: 99%
“…Two blood pressure readings were recorded with patients in the sitting position for at least 5 min, between 0900 and 1100 h in the morning; the average of the two readings was considered as the measurement for that visit; twenty-four hour ambulatory blood pressure monitoring (ABPM), by Spacelabs Inc. 90207 (Redmond Washington, USA), during a normal working day, as already published. 11 The monitor was fitted on in the morning, between 1000 and 1200 hours Subjects were asked to perform their normal daily activities and to consume their habitual diet. After calibration, the monitor was programmed to record BP and heart rate (HR) at 15-min intervals during the subjects' waking hours and at 20-min intervals during their usual sleeping hours.…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17] On the other hand, different results have been obtained in other reports. [18][19][20][21][22][23][24][25][26] Various studies have suggested that only about one-half to two-thirds of the variation in the anatomic extent of atherosclerosis and risk for atherosclerotic vascular disease can be explained by classic risk factors. 27,28 Therefore, new risk factors have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Many, but not all, of these studies have demonstrated increased LVMI in WCH subjects, with LVMI intermediate between that of subjects with normotension and those with sustained hypertension. [2][3][4][5][6][7][8][9][10][11][12][13] In addition, a recent study suggests that the long-term incidence of stroke may be elevated in adults with WCH. 14 Little is known about the clinical significance and natural history of WCH in children.…”
mentioning
confidence: 99%